Occurrence and characterization of NDM-5-producing Escherichia coli from retail eggs - Liu, Yi-Yun; Li, Tong; Yue, Huiying; Yue, Chao; Lu, Litao; Chen, Junqiang; Deng, Haotian; Gao, Xun; Liu, Jian-Hua (Frontiers in Microbiology, 2023)
The New Delhi Metallo-β-lactamase (NDM) producing Enterobacterales has been detected from diverse sources but has rarely been reported in retail eggs. In this study, 144 eggshell and 96 egg content samples were collected in 2022 from Guangdong province and were screened for NDM-producing strains. Four Escherichia coli strains (ST3014, ST10, ST1485, and ST14747) recovered from two (1.39%, 2 of 144) eggshells and two (2.08%, 2 of 96) egg content samples were identified as blaNDM−5-positive strains. Oxford Nanopore MinION sequencing and conjugation assays revealed that the blaNDM−5 gene was carried by IncX3 (n = 1), IncI1 (n = 1), and IncHI2 (n = 2). The IncI1-plasmid-carrying blaNDM−5 displayed high homology with one plasmid pEC6563-NDM5 from the human clinic, while the IncHI2 plasmid harboring blaNDM−5 shared highly similar structures with plasmids of animal origin. To the best of our knowledge, this is the first report on the identification of blaNDM−5-positive bacteria in retail eggs. NDM-producing E. coli could be transmitted to humans by the consumption of eggs or direct contact, which could pose a potential threat to human health.